Praktyka skutecznej pomocy rodzicom (rodzinie) w wybranych placówkach systemu oświaty - Ratajczak, Łukasz P. (Studia Edukacyjne, 2024)
The analyses presented in the article are based on theoretical considerations related to helping the family/parents/guardians of the wards of selected institutions of the educational system, as well as on the results of a pilot study on the experiences of the employees of these institutions in the practice of effectively helping the family to overcome the problems experienced.